Presidential Address: Sustainable Finance and ESG Issues—ValueversusValues - STARKS, LAURA T. (Journal of Finance, 2023)
ABSTRACT In this address, I discuss differences across investor and manager motivations for considering sustainable finance— value versus values motivations—and how these differences contribute to misunderstandings about environmental, social, and governance investment approaches. The finance research community has the ability and responsibility to help clear up these misunderstandings through additional research, which I suggest.